A DIACHRONIC CORPUS ANALYSIS OF GENDER REPRESENTATION IN DISNEY ANIMATED FILMS (2000–2023) - Abdul Jabar, Nor Fatin; Hassannuddin, Mohamad Iadid Ashrai; Ehsham, Nurul Iman Alwani (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
This research investigates the historical evolution of gender representation in Disney animated films from 2000 to 2023 through a corpus-linguistic analysis of 25 complete film scripts. This study utilizes collocational and keyword analyses to investigate the evolution of linguistic representations of male and female characters across three pivotal periods—2000–2010, 2011–2017, and 2018–2023—mirroring significant transformations in Disney’s narrative strategies and corporate priorities. Adjective collocates show that there are a lot fewer adjectives that describe how women look. For example, words like "lovely" and "sweet" fell by more than 40% from Period 1 to Period 3, while words that empower women, like "brave," "powerful," and "intellectual," rose by 55–70%. Male characters, typically associated with stoicism or action-oriented traits, demonstrate a significant rise in emotional vocabulary; the words emotional, vulnerable, and kind appear more than twice as frequently in the 2018–2023 subset as in the initial period. Keyword analysis shows that the difference between men and women is getting smaller. For example, hedging phrases in women’s speech go down, while strong verbs like "decide" and "lead" go up by more than 40%. This shows that women have more control over the story. Both genders are increasingly exhibiting traits such as strength and sensitivity, signifying a transition towards gender-neutral characterization. These linguistic modifications signify a broader ideological reorientation in Disney’s narratives, aligning with contemporary movements towards inclusivity and fair female representation. This research offers empirical evidence to feminist media studies and developmental psychology, demonstrating how corpus methodologies can uncover subtle yet substantial ideological shifts in children’s media discourse.